Modern and postmodern European film - Battista-Keser Ivana (Zbornik Radova Akademije Umetnosti, 2016)
The goal of the study is to give an overview of the characteristics of modern and postmodern film from 1950 to present day. Modernist films are pronouncedly constructed, full of interruptions, and visible seams in the storytelling process; they consist of poetical charges, individual poetics, and sudden cuts; they are directed towards the exploration of feelings rather than towards the presentation of the story; they can be realistic, theatrical, and minimalistic in form. Postmodernist film, created in the 1970s, developed from modernistic strategies; focuses on generating a discourse; has a tendency towards mainstream (commercial); there are also the less noticeable (by the rule non-commercial), which continue the tradition of artistic film; has a stronghold in documentary film, essayism, significant questions of identity, Otherness, gender, race, class; always implying some kind of recapitulation or rapture with the past, with an ideology.